Elemental analysis of soil and vegetation surrounding decomposing human analogues. Issue 3 (2nd July 2016) - Perrault, Katelynn A.; Forbes, Shari L.
ABSTRACT: The introduction of cadaveric material creates a localized surge of nutrients into the surrounding environment, which can have a profound effect on soil and vegetation in contact with the cadaver. Nutrient dynamics may assist in identifying the original deposition site of remains when scavenging has occurred, or where remains have been relocated to a secondary site in an attempt at concealment. The aim of this study was to characterize the nutrient input into the soil and vegetation surrounding decomposing pig ( Sus scrofa domesticus ) carcasses at an outdoor decomposition research facility in Southern Ontario. Soil and vegetation ( Agrostis gigantea ) samples were collected in a 2 m radial pattern from the carcasses. Significant elevation of percent water holding capacity, pH, soil-available phosphorus, and sodium were identified within a 20 cm radius and on occasion at 50 cm over three months. Potassium, calcium, and magnesium remained at baseline levels throughout the study. Increased nutrient availability could not be identified outside of the cadaver decomposition island (CDI), suggesting that nutrients may not easily pass through the CDI perimeter. Increased nutrient availability introduced by decomposing remains provides a means of chemical characterization of their original location, and could provide valuable information in death investigations.